(untitled) (Journal of Applied Oral Science, 2003)
The aim of this study was to evaluate the biocompatibility of blacks of organic bovine cancellous bone graft material (Gen-OxTM, Baumer) in ectopic sites. A cylinder of black of graft material measuring 5mm in diameter and 12mm in length was implanted in abdutor muscle of 30 Wistar rats. After 3, 7, 14, 21e 28 days, (6 animals/period) were killed, radiographies were taken and the tissues and blood were collected to histological and imunoglobuline G and M profile analysis, respectively. The analysis of the sections revelead an acute inflammatory process at 3 and 7 days, characterized by the presence of neutrophils. Absorption of the implanted matrix by mononuclear cells and scarce giant cells and their replacement by fibrous connective tissue rich in vessels and cells, was suggested. At 28 days, in most cases just remnants of the implanted matrix involved by the typical connective tissue of the perimisium were found. There was no radiographic evidence of mineral content or change in the IgG and IgM profile. On the basis in results described here, it could be concluded that the material is biocompatible and absorbable but, with no signs of osteoindutive capacity was observed.